EFFECTIVENESS OF RMT-BASED LEARNING TRAJECTORIES TO SUPPORT RELATIONAL UNDERSTANDING - Ifana, Bernika Indrialis; Aisyah, Nyimas; Susanti, Ely (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
Straight line equations are one of the mathematical materials that are often difficult to understand. This difficulty is due to a teaching approach that often emphasizes memorizing formulas without a deep understanding, as well as a lack of reasoning and problem-solving exercises. This study aims to design a learning trajectory of straight line equations using the Rigorous Mathematical Thinking (RMT) approach and its effectiveness on students' relational understanding. The research method used is design research, which focuses on designing a learning trajectory and consists of three stages: preliminary analysis, experiment, and retrospective which are carried out in two cycles. The subjects of this study were 8th grade students of Palembang State Junior High School, with 32 students as participants in the pilot experiment and 36 students as participants in the teaching experiment, which were selected by purposive sampling. Data is collected through observation, written tests, and interviews. The data from the HLT design will be analyzed qualitatively and  the results of the pre-test and post-test will be analyzed quantitatively. The results of this study produce a learning trajectory consisting of two main activities i.e Solving problems related to line equations that go through two points, and perpendicular line equations. The learning trajectory developed is able to support students' relational understanding, where in the learning process, students are directed to utilize the various knowledge they have, determine the most effective and efficient strategies, provide detailed solutions, and believe in the truth of the answers they use in solving problems. In addition, pre and post test results, there is an increase in relational understanding, it can be concluded that the RMT-based learning trajectory is effective for improving students' relational understanding of students in learning straight line equation material.Persamaan garis lurus merupakan salah satu materi matematika yang sering kali sulit dipahami. Kesulitan ini disebabkan oleh pendekatan pengajaran yang sering kali menekankan pada hafalan rumus tanpa pemahaman yang mendalam, serta kurangnya latihan penalaran dan pemecahan masalah. Penelitian ini bertujuan untuk merancang lintasan pembelajaran persamaan garis lurus menggunakan pendekatan Rigorous Mathematical Thinking (RMT) serta efektivitasnya terhadap pemahaman relasional siswa. Metode penelitian yang digunakan adalah penelitian desain, yang berfokus pada perancangan lintasan pembelajaran dan terdiri dari tiga tahap: analisis pendahuluan, eksperimen, dan retrospektif yang dilakukan dalam dua siklus. Subjek penelitian ini adalah siswa kelas 8 SMP Negeri Palembang, dengan 32 siswa sebagai peserta pilot eksperimen dan 36 siswa sebagai peserta eksperimen pengajaran, yang dipilih secara purposive sampling. Data dikumpulkan melalui observasi, tes tertulis, dan wawancara. Data hasil rancangan HLT akan dianalisis secara kualitatif dan hasil pre-test dan post-test akan dianalisis secara kuantitatif. Hasil penelitian ini menghasilkan lintasan pembelajaran yang terdiri dari dua kegiatan utama yaitu Menyelesaikan masalah yang berkaitan dengan persamaan garis yang melalui dua titik dan persamaan garis yang tegak lurus. Lintasan pembelajaran yang dikembangkan ini mampu mendukung pemahaman relasional siswa, dimana dalam proses pembelajaran siswa diarahkan untuk memanfaatkan berbagai pengetahuan yang dimiliki, menentukan strategi yang paling efektif dan efisien, memberikan solusi yang detail, serta meyakini kebenaran jawaban yang mereka gunakan dalam menyelesaikan masalah. Selain itu, hasil yang didapatkan adalah hasil pre-test dan post-test terdapat peningkatan pemahaman relasional, maka dapat disimpulkan lintasan belajar berbasis RMT efektif untuk meningkatkan pemahaman relasional siswa dalam pembelajaran materi persamaan garis lurus.